Automatic visual monitoring of welding procedure in stainless steel kegs. (May 2018) - Leo, Marco; Del Coco, Marco; Carcagnì, Pierluigi; Spagnolo, Paolo; Mazzeo, Pier Luigi; Distante, Cosimo; Zecca, Raffaele
Highlights: A system for automatic visual monitoring of welding process is introduced. It deals with monitoring of welding in dry stainless steel kegs for food storage. 5 kinds of defects are taken into consideration. It can work in critical conditions (inside the kegs). it does not use structured light making exploitable miniaturized hardware for data acquisition. Inspection performances have been evaluated by using a large set of kegs. Abstract: In this paper a system for automatic visual monitoring of welding process, in dry stainless steel kegs for food storage, is proposed. In the considered manufacturing process the upper and lower skirts are welded to the vessel by means of Tungsten Inert Gas (TIG) welding. During the process several problems can arise: 1) residuals on the bottom 2) darker weld 3) excessive/poor penetration and 4) outgrowths. The proposed system deals with all the four aforementioned problems and its inspection performances have been evaluated by using a large set of kegs demonstrating both the reliability in terms of defect detection and the suitability to be introduced in the manufacturing system in terms of computational costs.